UNIVERSALIDADE DO ATENDIMENTO À SAÚDE NO BRASIL: impasses e perspectivas - Janine Viera Teixeira (Universidade Federal do Maranhão, 2016)
The article discusses on the universal access to the Brazilian health system and its impediment. The Unified Health System ( Sistema Único de Saúde ; SUS) has been administrated by actions committed to capitalist management which impedes its full implementation. The universal access face problems as the dichotomy between the curative and preventive actions. The changes in the Health Law and in the Constitution (1988), for the introduction of the foreign capital, promote delays that cause failure in the system and leads to a defeated in the hearts and minds of the Brazilians. The increase in the private sector participation brings political consequences to the health system, because healthcare companies finance election campaigns. The state prioritizes the transfer of public money to the private sector. It concludes that public spending with health represented in the Gross National Product ( Produto Interno Bruto , PIB) do not reach half of the total spending on health. Nevertheless, resources are expended only with the poorest part of the population.